Mapping the Spatial and Seasonal Details of Heat Health Risks in Different Local Climate Zones: A Case Study of Shanghai, China - Lilong Yang; Chaobin Yang; Weiqi Zhou; Xueye Chen; Chao Wang; Lifeng Liu (Remote Sensing)
In the context of global climate change and rapid population growth, more people in cities are facing heat threats. Although health risk assessment is critical for reducing heat-related morbidity and mortality, previous studies have not accurately identified the spatial details of heat risk levels on a fine scale within a complete framework. Therefore, this study developed a systematic method to conduct a spatially explicit assessment of heat-related health risks using local climate zones (LCZs) in Shanghai, China. First, multisource data were used to map LCZs in Shanghai. Second, a modified temperature-humidity index, population density, and ecological parameters were employed to construct a heat hazard–exposure–vulnerability framework for heat risk assessment. Finally, the differences in heat-related health risks among LCZs were compared. The results indicate that in Shanghai (1) the LCZ concept could help estimate the heat health risk (HHR) at the fine block level, and the area proportion of LCZ5 (open mid-rise buildings) accounted for more than 50%; (2) detailed spatial patterns of heat risk levels were similar in spring, summer, and autumn, but different in winter due to seasonal variations in heat hazards; and (3) the built LCZs usually had higher heat risk levels than natural land cover LCZs, with LCZ2 (compact mid-rise), LCZ3 (compact low-rise), and LCZ5 facing the most serious heat risks. The high-rise LCZs might reduce the heat risk level in hot seasons owing to shading effects but add to this risk in winter. These findings contribute to our understanding of HHR assessment.